At her service - Spalding, Amy (Kensington Publishing Corp., 2024)
"Max Van Doren has a wish list, and a great career and a girlfriend are at the top. But despite being pretty good at her job as an assistant to one of Hollywood's fastest rising talent agents, she has no idea how to move up the ladder. And when it comes to her love life, she's stuck in perpetual lust for an adorably perfect bartender named Sadie. Her goals are clear--and Max has everything but the self-confidence to go for them...Tired of the sponcon life with its fake friends and endless selfies, Max realizes that to have true influence, she'll have to find the courage to make her own, totally authentic way in the world"--